Involvement of Toll-like Receptors in Ischemia-induced Neuronal Damage - Hamanaka, Junya; Hara, Hideaki (Central Nervous System Agents in Medicinal Chemistry, 2011)
Cerebral ischemia is characterized by obvious inflammatory cell aggregations, up-regulation of cytokine expression, and increased expression of intercellular adhesion molecules. Like systemic bacterial infections, cerebral injury is also associated with innate immunity, a specific immunologic response that utilizes Toll-like receptors (TLRs). The involvement of TLRs in cerebral ischemia is now being confirmed using animal models. Recent reports reveal that mice that lack TLR2 and TLR4 show improved stroke outcomes and that TLR2 and 4 may contribute to neuronal injury that occurs after cerebral ischemia. In this review, we have summarized these recent reports concerning the association of TLRs with cerebral ischemia.
Keywords: IRF3